From financial literacy to financial satisfaction: The mediating role of financial behavior - Maftuhah, Rifa’atul; Wardoyo, Cipto; Pratikto, Heri; Churiyah, Madziyatul (Edelweiss Applied Science and Technology, 2025)
The development of financial technology (fintech) and increased access to financial services, along with changes in consumption patterns, have significantly impacted individual perceptions of financial satisfaction (FS). Challenges to financial satisfaction include economic instability, inflation, and income disparity. This study aims to examine the relationship between financial literacy (FL) and financial risk tolerance (FRT) on financial satisfaction (FS), considering the mediating role of financial behavior (FB). The research was conducted on 383 teachers across five major cities in East Java, Indonesia—Surabaya, Sidoarjo, Gresik, Mojokerto, and Pasuruan—using proportional random sampling. Data collected were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings revealed that both financial literacy (FL) and financial risk tolerance (FRT) positively influence teachers' financial satisfaction (FS). Additionally, financial behavior (FB) was found to mediate the relationship between financial literacy (FL) and financial satisfaction (FS), as well as between financial risk tolerance (FRT) and FS. This research is expected to contribute both theoretically and practically by emphasizing the importance for policymakers in the education sector to develop financial well-being programs for teachers and highlighting the need for teachers to prioritize financial components in their personal and professional lives.